Vikings. Season 2 [videorecording (DVD)] - Winnick, Katheryn; Gilsig, Jessalyn, 1971-; Standen, Clive ([Publisher not identified], 2014)
Armed with more power and greater responsibility, Ragnar's desire to seek out and conquer new kingdoms remains unquenchable. Loyalties shift as friends turn to foes and unlikely alliances are formed. Amidst all the war and political confusion, not a single soul is spared in the name of supremacy.